Implementation Of SCM Information System At Street Coffee For Optimization Of Distribution Stock Control - Rizka Fadhila; Nofriadi Nofriadi; Febby Madonna Yuma (Brilliance: Research of Artificial Intelligence, 2026)
The development of information technology has significantly influenced business operations, particularly in supply chain management (SCM), which requires efficient, accurate, and integrated systems to support decision-making processes. However, many small and medium enterprises still rely on manual data processing, which can lead to inefficiencies and operational constraints. At Street Coffee, inventory management and raw material distribution are still handled manually, resulting in discrepancies between recorded and actual stock levels, delays in procurement processes, limited real-time monitoring, and difficulties in coordinating with suppliers. These issues negatively impact operational efficiency and service quality. This study aims to design and implement a web-based SCM information system to improve inventory control, enhance data accuracy, and optimize distribution processes. The research employs a qualitative approach, with data collection methods including observation, interviews, and documentation. System development is carried out using Unified Modeling Language (UML) for system design and database modeling to ensure structured data management. The results indicate that the implemented system successfully integrates inventory, supplier, and distribution data into a centralized platform. The system enables real-time stock monitoring, minimizes data entry errors, improves coordination between procurement and inventory processes, and supports faster and more accurate decision-making. Therefore, the implementation of the SCM system contributes significantly to improving operational efficiency, effectiveness, and overall business performance at Street Coffee.